A generic framework to assess the representation and protection of benthic ecosystems in European marine protected areas. Issue 7 (5th July 2020) - Greathead, Clare; Magni, Paolo; Vanaverbeke, Jan; Buhl‐Mortensen, Lene; Janas, Urszula; Blomqvist, Mats; Craeymeersch, Johan A.; Dannheim, Jennifer; Darr, Alexander; Degraer, Steven; Desroy, Nicolas; Donnay, Annick; et al.
Abstract: There is concern across the International Council for the Exploration of the Sea (ICES) region that a consideration of vulnerable components and the wider support mechanisms underpinning benthic marine ecosystems may be lacking from the process of marine protected area (MPA) designation, management and monitoring. In this study, MPAs across six European ecoregions were assessed from a benthic ecology perspective. The study included 102 MPAs, designated by 10 countries, and focused on three aspects regarding the role of the benthos in: (i) the designation of MPAs; (ii) the management measures used in MPAs; and (iii) the monitoring and assessment of MPAs. Qualitative entries to a questionnaire based on an existing framework (EU project 'Monitoring Evaluation of Spatially Managed Areas', (MESMA) were collected by 19 benthic experts of the ICES Benthic Ecology Working Group. A pedigree matrix was used to apply a numerical scale (score) to these entries. The results showed clear differences in scores between ecoregions and between criteria. The designation‐phase criteria generally achieved higher scores than the implementation‐phase criteria. Poor designation‐phase scores were generally reiterated in the implementation‐phase scores, such as scores for assessment and monitoring. Over 70% of the MPA case studies were found to consider the benthos to some extent during selection and designation; however, this was not followed up with appropriate management measures and good practice during the implementation phase. Poor spatial and temporal coverage of monitoring and ineffective indicators is unlikely to pick up changes caused by management measures in the MPA. There is concern that without adequate monitoring and adaptive management frameworks, the MPAs will be compromised. Also, there could be an increased likelihood that, with regard to the benthos, they will fail to meet their conservation objectives. This assessment was successful in highlighting issues related to the representation and protection of the benthos in MPAs and where changes need to be made, such as expanding the characterization and monitoring of benthic species or habitats of interest. These issues could be attributable to an ongoing process and/or an indication that some MPAs only have 'paper protection'.